Acute intermittent porphyria with syndrome of inappropriate antidiuretic hormone secretion (SIADH) and neurological crisis, successfully treated with haemodialysis - Singh, P. S.; Rawat, Ramakant; Zafar, K. S. (International Journal of Research in Medical Sciences, 2017)
We report a 35 years old male, a case of Acute Intermittent Porphyria (AIP) with Syndrome of Inappropriate Antidiuretic Hormone secretion (SIADH) and neurological crisis for its rarity. Since specific parenteral medication (hemin) was not available, patient was empirically treated with haemodialysis with satisfactory outcome.